On-call work and depressive mood: A cross-sectional survey among rural migrant workers in China - Xu, Qingqing; Wang, Liyun; Zhang, Yiwen; Jiang, Xia (Frontiers in Psychology, 2023)
With the rapid development of China's "gig economy", the on-call work model has grown increasingly prevalent in China and has attracted a large number of rural migrant workers with its low employment threshold. However, this irregular employment mode may negatively impact the mental health of workers. This paper uses an ordinal logistic regression model to study the relationship between Chinese rural migrant workers' on-call work and their depression. The results showed that after controlling for relevant variables, the odds ratio of depressive mood among rural migrant workers engaged in on-call work was 1.22 (95% CI 1.04-1.43) compared with rural migrant workers who did not need to be on call. In further heterogeneity research, we found that on-call work is more likely to aggravate the depression risk of rural migrant workers who are highly dependent on the internet and have low-wage incomes. This research suggests that appropriate measures should be taken to mitigate the negative impact of on-call work on the mental health of rural migrant workers, and more attention needs to be paid to the mental health of lower salaried and gig workers. This paper provides a valuable sample of Chinese rural migrant workers for theoretical research on the relationship between on-call work and mental health and confirms the relationship between the two. These results contribute new ideas to the theory and practice of psychological crisis intervention aimed at Chinese rural migrant workers.